TourMuOve application: interactive navigation and mobile application in creating efficient tourist movement in Muar, Johor - Che Azimi, Amin Mustaqim; Farudz, Baiduri Zaiyanna; Mohd Rosdan, Khairunnissa; Hamidi, Nurul Hassanah; Noor Azman, Nor Afifin Nadia; Roslim, Nordanish Sofea Illyana; Abd Rahman, Nur Hidayah (Research Management Unit (RMU), Universiti Teknologi MARA Cawangan Pulau Pinang 13500 Permatang Pauh, Penang, 2019)
Unacknowledged of tourist movement among locals and inefficient marketing strategy leads to unawareness of tourist attraction in Muar, Johor. Thus, this paper intended to introduce a mobile application named movement to promote available attractions in Muar, Johor. The study focuses on motivations, interest and compositions, the timing of visits and the destination knowledge as well as the emotional value of the places among tourists. A data collection has been executed at Muar, Johor in order to gather the tourist attraction pattern, as well as intra-destination movement in aspect of trip and personal characteristic among visitors. This application comprises the features that will help tourist to efficiently travel in Muar town. The features help the tourist to navigate the most preferred places acquired by them. "TourMuOve" included a game named "MuoJom" which is similar to Augmented Reality game namely "PokemonGo". This game can assist businesses collaboration with locals' restaurants and stalls to give away free vouchers and discounts in the games. In return, more tourists and visitors will drop by to their shops to redeem the vouchers and enjoy catching vouchers while visiting the attraction areas. This application will benefit Muar in terms of promoting Muar and increasing its tourist arrival.